Glycine functionalized magnetic nanoparticle entrapped calcium alginate beads: A promising adsorbent for removal of Cu(II) ions. Issue 2 (June 2016) - Asthana, Anupama; Verma, Renu; Singh, Ajaya Kumar; Susan, Md. Abu Bin Hasan
Graphical abstract: Highlights: GFMNPs were synthesized and fabricated with alginate beads for removal of Cu(II). The new adsorbent shows high capacity for the removal of Cu(II) ions. The adsorbent exhibits good magnetic separation and excellent reproducibility. The methodology is cost effective and involves an eco-friendly procedure. The adsorbent has high surface area and large number of active groups on the surface. Abstract: Glycine functionalized magnetic nanoparticle entrapped calcium alginate beads (GFMNPECABs) were successfully prepared and used as a novel adsorbent for removal of Cu(II). The adsorbent was characterized by Fourier transform infrared (FTIR) spectroscopy, dynamic light scattering (DLS) measurements, scanning electron microscopy (SEM), x-ray diffraction (XRD) and Brunauer-Emmett-Teller (BET) surface area analysis. Magnetic nanoparticles (MNPs) could be successfully functionalized by glycine and glycine functionalized magnetic nanoparticles (GFMNPs) could be entrapped into the alginate biopolymer. BET result showed specific high surface area and mesoporous structure of the adsorbent. The adsorption capacity of GFMNPECABs for Cu(II) ions evaluated by batch adsorption experiments showed maximum value of 120 mg/g at pH 6 in 160 min. Adsorption isotherms well fitted to different available models and data could be best described by Langmuir model. The adsorption kinetics followed pseudo second order model well. The thermodynamic studies showed exothermic and spontaneous nature of Cu(II) adsorption.